2021
DOI: 10.3390/metabo11050261
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of Metabolite Profiles in Pigs Depends on the Genetic Background

Abstract: The study aimed to investigate possible systematic effects in the basic underlying variability of individual metabolomic data. In this context, the extent of gender- and genotype-dependent differences reflected in the metabolic composition of three tissues in fattening pigs was determined. The 40 pigs belonged to the genotypes PIx(LWxGL) and PIxGL with gilts and boars, respectively. Blood and tissue samples from M. longissimus dorsi and liver were directly taken at the slaughtering plant and directed to GC × G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Studies on pigs have found that the heritability of long-chain polyunsaturated fatty acids in pork is above 0.50 [ 26 ], and the heritability of lipid metabolism molecules in the backfat of Iberian pig ranges from 0.06 to 0.53 [ 27 ]. There are differences in liver and blood metabolites among different pig breeds and are associated with meat quality indicators [ 28 ]. To date, there is no relevant article directly expounding the relationship between plasma metabolites and breeding traits in pigs, but there were also many articles reporting that plasma metabolites were associated with related indicators such as body weight [ 29 ], growth rate [ 30 , 31 ], fat deposition [ 20 ], and reproductive performance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on pigs have found that the heritability of long-chain polyunsaturated fatty acids in pork is above 0.50 [ 26 ], and the heritability of lipid metabolism molecules in the backfat of Iberian pig ranges from 0.06 to 0.53 [ 27 ]. There are differences in liver and blood metabolites among different pig breeds and are associated with meat quality indicators [ 28 ]. To date, there is no relevant article directly expounding the relationship between plasma metabolites and breeding traits in pigs, but there were also many articles reporting that plasma metabolites were associated with related indicators such as body weight [ 29 ], growth rate [ 30 , 31 ], fat deposition [ 20 ], and reproductive performance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%